Taxonomic reassessment of bats from the Western Himalayas, India and description of a new species of the Myotis frater complex (Mammalia, Chiroptera, Vespertilionidae) - Saikia, Uttam; Chakravarty, Rohit; Csorba, Gabor; Laskar, Mostaque Ahmed; Ruedi, Manuel (Zootaxa, 2025)
Based on specimens collected during recent field surveys and re–examination of museum specimens, we critically reviewed the taxonomic status of several bat species occurring in the Western Himalayan states of Himachal Pradesh and Uttarakhand in India. The present review incorporates both morphological and molecular data and additionally illustrates new echolocation call characters of some little–known species from the region. A new species, Myotis himalaicus sp. nov., belonging to the My. frater complex is described based on multiple evidence of unique characters. We revised putative records of Tadarida teniotis as Ta. insignis and report this species for the first time from India. We also detail the first occurrence of Rhinolophus nippon, Hypsugo savii and My. sicarius from the Western Himalayas. We conclusively delineate Pipistrellus babu occurring in the Western Himalayas as a species distinct from Pi. javanicus in Southeast Asia and draw attention to several species–complexes (i.e. Rhinolophus macrotis, Eptesicus pachyomus, Murina cyclotis or Mu. huttonii) where further material and analyses are needed to clarify the species boundaries.